2019
DOI: 10.1101/681668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclin binding Cy motifs have multiple activities in the initiation of DNA replication

Abstract: The initiation of DNA replication involves the cell cycle-dependent assembly and disassembly of protein complexes, including the Origin Recognition Complex (ORC) and CDC6 AAA+ ATPases. We report that multiple short, linear protein motifs (SLiMs) within intrinsically disordered regions in ORC1 and CDC6, including Cyclin-binding (Cy) motifs, mediate Cyclin-CDK dependent and independent protein-protein interactions, conditional on cell cycle phase. The ORC1 Cy motif mediates an auto-regulatory self-interaction, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 86 publications
(96 reference statements)
2
9
0
Order By: Relevance
“…In line with this idea, we show that human Cdt1, like Dm Cdt1, forms condensates in a DNA-dependent manner (Figure 2—figure supplement 1G). A recent report demonstrating an essential function for the phosphorylation-regulated conversion of intramolecular IDR interactions in human Orc1 to intermolecular interactions between ORC and Cdc6 IDRs (Hossain et al, 2019) is similarly supportive with such a proposal (Figure 6). We anticipate that these interactions, possibly augmented by other transient IDR-IDR interactions forming in both cis and trans , facilitate some form of condensation or localized clustering of initiation factors for the functional assembly of pre-RCs.…”
Section: Discussionsupporting
confidence: 66%
“…In line with this idea, we show that human Cdt1, like Dm Cdt1, forms condensates in a DNA-dependent manner (Figure 2—figure supplement 1G). A recent report demonstrating an essential function for the phosphorylation-regulated conversion of intramolecular IDR interactions in human Orc1 to intermolecular interactions between ORC and Cdc6 IDRs (Hossain et al, 2019) is similarly supportive with such a proposal (Figure 6). We anticipate that these interactions, possibly augmented by other transient IDR-IDR interactions forming in both cis and trans , facilitate some form of condensation or localized clustering of initiation factors for the functional assembly of pre-RCs.…”
Section: Discussionsupporting
confidence: 66%
“…The fact that Cdt1-Cy has the highest activity of all the variants tested here may be a reflection of that additional negative regulation in the so-called “PEST domain.” In our experiments, Cdt1 chromatin binding is barely detectable which is consistent with the transient Cdt1 residence at origins during budding yeast MCM loading in vitro [ 68 , 73 ]. Alternatively, the Cy motif mutation may disrupt more than only Cyclin binding such as has been recently reported for ORC [ 74 ]. Clearly the spectrum of Cdt1 biological activities can be tuned by combinations of phosphorylations and dephosphorylations, and continued in-depth analyses will yield additional insight into Cdt1 regulation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found there were functionally essential regions in the lesser conserved IDR regions of both ORC1 and ORC2. Our lab has recently reported that a Cyclin-motif bearing region of ORC1 (180 - 240 aa) is essential for binding to CDC6 at the right time during the cell cycle to enable pre-RC formation (Hossain et al, 2019). And similarly, based on homology, a previously identified putative NLS motif (Lidonnici et al, 2004) also had hits nominating that region as essential in our ORC1 screen (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…The known functional domains in ORC1, including the BAH, AAA+ and WHD were identified using the open reading frame tiling CRISPR-Ca9 sgRNA screen, as well as other regions of ORC1, including the intrinsically disordered region (IDR; amino acids 180-480, Figure 1e) which we know binds Cyclins E and A-CDK2 and CDC6 (Hossain et al, 2019) as well as many other proteins we have identified and are characterizing in detail. The screen also identified an essential region of ORC1 in and around amino acid 750-790 (Figure 1a-b) which may represent the pericentrin- AKAP450 centrosomal targeting (PACT) domain that localizes ORC1 to centrosomes to regulate correctly centrosome and centriole copy number (Hemerly et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation